The Danielic discourse on empire in Second Temple literature - Frisch, Alexandria. (Supplements to the Journal for the Study of Judaism, 2016)
In The Danielic Discourse on Empire in Second Temple Literature , Alexandria Frisch asks: how did Jews in the Second Temple period understand the phenomenon of foreign empire? In answering this question, a remarkable trend reveals itself-the book of Daniel, which situates its narrative in an imperial context and apocalyptically envisions empires, was overwhelmingly used by Jewish writers when they wanted to say something about empires. This study examines Daniel, as well as antecedents to and interpretations of Daniel, in order to identify the diachronic changes in perceptions of empire during this period. Oftentimes, this Danielic discourse directly reacted to imperial ideologies, either copying, subverting, or adapting those ideologies. Throughout this study, postcolonial criticism, therefore, provides a hermeneutical lens through which to ask a second question: in an imperial context, is the Jewish conception of empire actually Jewish?